Effects of remote ischemic preconditioning on platelet activation and reactivity in patients undergoing cardiac surgery using cardiopulmonary bypass: a randomized controlled trial. (2nd January 2022) - Cho, Youn Joung; Nam, Karam; Yoo, Sol Ji; Lee, Seohee; Bae, Jinyoung; Park, Ji-Young; Kim, Hang-Rae; Kim, Tae Kyong; Jeon, Yunseok
Abstract: During cardiopulmonary bypass (CPB), platelet activation and dysfunction are associated with adverse outcomes. Remote ischemic preconditioning (RIPC) has been shown to attenuate platelet activation. We evaluated the effects of RIPC on platelet activation during CPB in patients undergoing cardiac surgery. Among 58 randomized patients, 26 in the RIPC group and 28 in the sham-RIPC group were analyzed. RIPC consisted of 4 cycles of 5-min ischemia induced by inflation of pneumatic cuff pressure to 200 mmHg, followed by 5-min reperfusion comprising deflation of the cuff on the upper arm. Platelet activation was assessed using flow cytometry analysis of platelet activation markers. The primary endpoint was the AUC of CD62P expression during the first 3 h after initiation of CPB. Secondary outcomes were the AUC of PAC-1 expression and monocyte-platelet aggregates (MPA) during 3 h of CPB. The AUCs of CD62P expression during 3 h after initiation of CPB were 219.4 ± 43.9 and 211.0 ± 41.2 MFI in the RIPC and sham-RIPC groups, respectively (mean difference, 8.42; 95% CI, −14.8 and 31.7 MFI; p =.471). The AUCs of PAC-1 expression and MPA did not differ between groups. RIPC did not alter platelet activation and reactivity during CPB in patients undergoing cardiac surgery.